The Potency of Soil Insect As Soil Quality Bioindicators in Citrus Plantations Poncokusumo District, Malang Regency - Suheriyanto, Dwi; Lutfiyah, Arifatul; Dara W., Dika; Farhan, Mohammad; Izzah, Ainiy (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2020)
Insects have great potential to be used as soil bioindicators. The research aims to analyze abundance and diversity of soil insects genus and determine the soil insects genus that have potential as soil quality bioindicators in citrus plantations. The study was conducted in conventional and semiorganic citrus plantations in Poncokusumo District, Malang Regency. The research used pitfall trap and hand sorted methods. Data were analyzed to find out diversity index, Canonical Correspondence Analysis and Indicator Value Index. The data analysis used PAST program version 3.15 and software R. The research results were obtained 20 genus of soil insects. The highest abundance of soil insects is occupied by the genus Aphaenogaster. The diversity of soil insects in semiorganic citrus plantations is higher than conventional citrus plantations. The soils insects that have potential as bioindicators of soil quality in conventional citrus plantations is the genus Formica, while in the semiorganic citrus plantations are the genus Cyrtepistomus, Pangeus, Tenebrio, Euborellia, Allonemobius, Stelidota, Gryllus and Chlaenius.